An Evaluation of Drug Storage Practices in the Pharmacy Warehouse of Parapat Regional General Hospital, Girsang Sipangan Bolon District, Simalungun Regency - Saide Pramita Sijabat; Denita Denita; Frima Lumban Gaol (Jurnal EduHealth, 2026)
Drug storage is an activity of storing and maintain by placing the drugs received in a place that is considered safe from theft and physical disturbances that can damage the quality of drugs and medical supplies. This study aims to determine the suitability of the drug storage system at the Parapat Regional General Hospital with the standards of the Regulation of the Ministry of Health of the Republic of Indonesia No. 72 of 2016 with storage indicators. Drug storage carried out by pharmacists has various purposes, one of which is to make it easier for officers to find drugs to be used. With organized and neat storage, it can shorten the time to find the medicines you need. This type of research is descriptive observational and the tool used in this study is an observation sheet related to drug storage at Parapat General Hospital as a data collection tool. The results showed that the drug storage requirements did not meet the requirements because APAR is not yet aveilable. The percentage of matched drugs with stock cards and drug storage systems has not met the standard, because the percentage obtained is 99.10% where the standard that must be met is 100%.  while the Turn Over Ratio value is 4,38 times, the percentage of expired and damaged drugs is 2,09% . the data still does not meet the existing requirements. Then it was concluded that the storage of drugs at the Parapat Regional General Hospital still does not meet the requirements in accordance with the Regulation of the Ministry of Health of the Republic of Indonesia No. 72 of 2016